Aversion to the World in Nasser Khosrow's Poems - Mujadadi, Mirsubhan; Hammad, Fazil Ahmad (Integrated Journal for Research in Arts and Humanities, 2023)
Apostasy is one of the main topics in Persian poetry and literature. Nasser Khosrow believes that the virtue of man is to pay attention to the impermanence and mortality of material manifestations, and those who are captives of the world and worldly belongings; He considers it a disgrace. Perhaps it can be said that in the complete biography of the worldly and ascetic poetry of Dari Persian literature, Nasser Khosrow is Kesai and the peak of it is Sana'i. The high frequency of worldly aversion theme in the poem is dependence on the court and their abandonment. The images of the world in the mind of Nasser Khosrow; It is well conveyed through the dictionary. These pictures show its true face. Nasser Khosrow's depiction of the world is not only ugly and unpleasant; Sometimes he looks wise. It should be said that the poet has given many advices on leaving the world and worldly desires, the main reason for which is the impermanence and transience of the world.